Trade, currencies and finance - Goldstein, Morris 1944- (World Scientific Publishing Co. Pte Ltd., 2017)
"The book includes selected papers of Morris Goldstein on the following topics in international macroeconomics: international trade, currency regimes, exchange rate policy, international policy coordination, banking, financial crises, financial regulation, IMF policies, and China's exchange rate policy. Some of the papers are empirical in nature, while others address key policy issues in international macroeconomics. Many of the papers are co-authored with other well-known international economists, including Jacob Frenkel, Mohsin Khan, Nicholas Lardy, Peter Montiel, Michael Mussa, Carmen Reinhart, and Philip Turner, among others. Taken as a group, the papers should give the reader a good picture of many of the most important issues in international macroeconomics over the past 35 years."--Publisher's website
Title from PDF title page (viewed June 10, 2017)
Keywords: International trade; Foreign exchange; Banks and banking, International / Law and legislation; Electronic books; Weltwirtschaft; Welthandel